2010
DOI: 10.1017/s0950268810001111
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for community-associatedStaphylococcus aureusinfections: results from parallel studies including methicillin-resistant and methicillin-sensitiveS. aureuscompared to uninfected controls

Abstract: Despite the increasing burden of community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) infections, the risk factors are not well understood. We conducted a hypothesis-generating study using three parallel case-control studies to identify risk factors for CA-MRSA and community-associated methicillin-susceptible S. aureus (CA-MSSA) infections. In the multivariate model, antimicrobial use in the 1-6 months prior to culture was associated with CA-MRSA infection compared to CA-MSSA [adjusted od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 40 publications
5
23
1
Order By: Relevance
“…In our study, we evaluated the 6 "Cs" of potential risk factors for CA-MRSA and found few differences when compared with CA-MSSA. Similar to previous findings, neither crowding nor cleanliness distinguished CA-MRSA from CA-MSSA infection [28,29]. While others have found a significant association between prior antibiotic use and CA-MRSA (vs CA-MSSA), we did not [28].…”
Section: Continuedsupporting
confidence: 84%
See 2 more Smart Citations
“…In our study, we evaluated the 6 "Cs" of potential risk factors for CA-MRSA and found few differences when compared with CA-MSSA. Similar to previous findings, neither crowding nor cleanliness distinguished CA-MRSA from CA-MSSA infection [28,29]. While others have found a significant association between prior antibiotic use and CA-MRSA (vs CA-MSSA), we did not [28].…”
Section: Continuedsupporting
confidence: 84%
“…Similar to previous findings, neither crowding nor cleanliness distinguished CA-MRSA from CA-MSSA infection [28,29]. While others have found a significant association between prior antibiotic use and CA-MRSA (vs CA-MSSA), we did not [28]. The few significant associations we noted were with CA-MSSA infection (vs CA-MRSA).…”
Section: Continuedsupporting
confidence: 81%
See 1 more Smart Citation
“…Other sites include any lesions, manipulated sites (such as intravenous and urinary catheters), the axillae, the fingertips and the hairline. The latter two sites can provide clues that patients are dispersers with an increased risk of transmission to other patients, family members or the wider environment around patient areas or the home [19,20]. Pooling swabs from several sampling sites into a single broth culture has long been advocated as a cost-effective screening method where one just wants to know whether, rather than where, subjects are positive [21].…”
Section: Universal and Targeted Screeningmentioning
confidence: 99%
“…These infections have been especially frequent in certain high-risk groups such as military recruits, prison and jail inmates, athletes, and children in daycare (reviewed in reference 1). Common risk factors associated with CA-MRSA include sharing of personal items, superficial abrasions, crowding, limited access to showers, and exposure to others with MRSA infections (3)(4)(5)(6).…”
mentioning
confidence: 99%